Unsymmetrical β-diketiminate magnesium(i) complexes : syntheses and application in catalytic hydroboration of alkyne, nitrile and carbonyl compounds - Li, Jia (2020)
A series of unsymmetrical β-diketimine coordinated magnesium(i) complexes have been successfully synthesized via reductions of related magnesium(ii) halide complexes with a sodium reducing reagent in toluene or n-hexane solution. All the unsymmetrical magnesium(i) complexes prepared have been crystallographically and spectroscopically characterized. It was found, for the first time, that these well-defined unsymmetrical magnesium(i) complexes were highly active pre-catalysts for the hydroboration of alkynes, nitriles, aldehydes and ketones.